Peran Edukasi Digital dalam Menekan Budaya Konsumtif Fast Fashion: Studi Kasus Akun Tiktok Dino Augusto - Juanda, Dhiemas Permana; Noviriani, Eliza; Roshani, Roshani (Politeknik Raflesia Press, 2025)
This study aims to explore the impact of fast fashion trends on TikTok, focusing on the educational content presented by Dino Augusto (@dosen_fasyun) and its influence on digital consumer culture from a behavioral accounting perspective. Employing a qualitative netnographic approach and NVivo 15 Plus software, the research analyzed user interactions in TikTok video comment sections, supported by Word Cloud and Mind Map visualizations. The data were categorized into seven key themes: consumptive behavior, drivers of fast fashion consumption, the fast fashion industry system, environmental impacts of fast fashion, alternatives to fast fashion consumption, raising consumer awareness through education, and rejection of fast fashion. Findings indicate that educational content effectively increases critical awareness about the harmful effects of fast fashion, including labor exploitation, environmental degradation, and excessive consumerism. Informative, authentic content aligned with the creator’s expertise significantly influences audience attitudes and behaviors. The study concludes that educational use of social media can foster more responsible consumption patterns and reduce the negative consequences of fast fashion. This research contributes to the field of behavioral accounting and digital humanities by illustrating how online educational content shapes consumer decision-making. It emphasizes the importance of continued social media-based education to encourage sustainable financial behavior and ethical fashion choices.